HUBUNGAN SOSIAL EKONOMI ANTARA TAUKE DAN PETANI KARET DI DESA PANGKALAN SERIK KECAMATAN SIAK HULU KABUPATEN KAMPAR - Maya Utari; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Pangkalan Serik Village, Siak Hulu District, Kampar District. This study aims to find out the Social Economic Relationship between Tauke and Rubber Farmers in Pangkalan Serik Village, Siak Hulu District, Kampar District. The main problem in this research is how the socio-economic relationship between tauke and rubber farmers in Pangkalan Serik Village and what factors influence the socio-economic relationship between tauke and rubber farmers in Pangkalan Serik Village. Sampling in this research is by technique of full enumeration sampling or census method. The number of sample is 47 respondents. The method used is descriptive quantitative method with descriptive analysis. Data filtering instruments used are observation, questionnaire and documentation. The result of this research is general:the form of socio-economic relationship between tauke and rubber farmers in the village of Pangkalan Serik is the relationship of buying and salling, the relationship of accounts payable, and social relations in the form of assistance from tauke to rubber farmers. Factors that affect the socio-economic relationship between tauke and rubber farmers in Pangkalan Serik Village are family relationship, neighboring relationship, know relationship, long sell rubber latex to tauke in the village of Pangkaln Serik.Keywords: Social Relations, tauke and rubber farmers, in Pangkalan Serik Village